2021
DOI: 10.1186/s13037-021-00305-6
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute myocardial infarction after elective spinal fusions or joint replacement surgery in the United States: a large-scale retrospective observational cohort study in 322,585 patients

Abstract: Background Acute myocardial infarction (AMI) is an uncommon but fatal complication among patients undergoing elective spinal fusion surgery (SF), total hip arthroplasty (THA), and total knee arthroplasty (TKA). Our objective was to estimate the incidence of AMI among adults undergoing elective SF, THA, and TKA in different post-operative risk windows and characterize high-risk sub-populations in the United States. Methods A retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies have suggested an association between spinal fusion and vascular-related conditions (Arena et al, 2021;Marquez-Lara et al, 2014;Xu et al, 2013). However, previous cohort studies have reported little or no significant association (Wu et al, 2012); thus, this topic remains controversial.…”
Section: Spine Fusion and Vascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested an association between spinal fusion and vascular-related conditions (Arena et al, 2021;Marquez-Lara et al, 2014;Xu et al, 2013). However, previous cohort studies have reported little or no significant association (Wu et al, 2012); thus, this topic remains controversial.…”
Section: Spine Fusion and Vascular Complicationsmentioning
confidence: 99%
“…These elements combine to create a heightened risk of vascular complications following spinal fusion surgeries. Some studies have suggested an association between spinal fusion surgery and vascular-related conditions (Arena et al, 2021; Marquez-Lara et al, 2014; Reeg, 2001; Swann et al, 2016; Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial infarction (MI) is a major cause of global morbidity and mortality that affects nearly 800,000 patients each year in the United States alone. 1 Cardiac wound healing after MI is a complex and multiphase process that begins with necrosis and apoptosis of cardiomyocytes due to ischemic injury with or without reperfusion followed by the formation of a fibrotic scar. 2 The acute phase of this process involves an inflammatory response and degradation of the extracellular matrix (ECM) followed by collagen synthesis, organization, and deposition within the first few weeks after MI.…”
mentioning
confidence: 99%